Multilingual education for social justice: globalising the local - Ajit K Mohanty (ed.) (New Delhi : Orient Blackswan, 2009)
Contributed papers presented at the International Conference on Multilingual Education: Challenges, Perspectives, and Opportunities, held at the Zakir Husain Centre for Educational Studies, Jawaharlal Nehru University, New Delhi in February 2008, organized by UNICEF and others.
Keywords: Multilingualism; Multicultural Education; Education; Social Sciences